Evolutionary history of a relict conifer, Pseudotaxus chienii (Taxaceae), in south-east China during the late Neogene: old lineage, young populations. (25th November 2019) - Kou, Yixuan; Zhang, Li; Fan, Dengmei; Cheng, Shanmei; Li, Dezhu; Hodel, Richard G J; Zhang, Zhiyong
Abstract: Background and Aims: Many monotypic gymnosperm lineages in south-east China paradoxically remain in relict status despite long evolutionary histories and ample opportunities for allopatric speciation, but this paradox has received little attention and has yet to be resolved. Here, we address this issue by investigating the evolutionary history of a relict conifer, Pseudotaxus chienii (Taxaceae). Methods: DNA sequences from two chloroplast regions and 14 nuclear loci were obtained for 134 samples. The demographic history was inferred and the contribution of isolation by environment (IBE) in patterning genetic divergence was compared with that of isolation by distance (IBD). Key Results: Three genetic clusters were identified. Approximate Bayesian computation analyses showed that the three clusters diverged in the late Pliocene (~3.68 Ma) and two admixture events were detected. Asymmetric gene flow and similar population divergence times (~ 3.74 Ma) were characterized using the isolation with migration model. Neither IBD nor IBE contributed significantly to genetic divergence, and the contribution of IBE was much smaller than that of IBD. Conclusions: These results suggest that several monotypic relict gymnosperm lineages like P. chienii in south-east China did not remain in situ and undiversified for millions of years. On the contrary, they have been evolving and the extant populations have become established more recently, having insufficient time to speciate. Our findings provide a new perspective for understanding the formation and evolution of the relict gymnosperm flora of China as well as of the Sino-Japanese Flora.